What can we learn from past and recent Bavarian knowledge for the future development of European veterinary herbal medicine? An ethnoveterinary study. (24th April 2022) - Schlittenlacher, Theresa; Knubben-Schweizer, Gabriela; Dal Cero, Maja; Vogl, Christian R.; Maeschli, Ariane; Hamburger, Matthias; Walkenhorst, Michael
Abstract: Ethnopharmacological relevance: While the interest in finding medical solutions for the worldwide antibiotics crisis is rising, the legal possibility of simplified authorization of herbal veterinary medicinal products is dwindling. An important basis for both the preservation and development of knowledge in veterinary herbal medicine are pharmacological and clinical studies on the performance of herbal remedies, based on historical written sources on the treatment of farm animals with medicinal plants, as well as current ethnoveterinary research. Nevertheless, there is only limited systematic ethnoveterinary research in Europe, with the exceptions of the Mediterranean region, Switzerland and Austria. We conducted a survey on the ethnoveterinary knowledge of farmers in Bavaria, and analyzed two regional historical textbooks. Aim of the study: We documented the local veterinary knowledge about livestock in Bavaria based upon local historical textbooks and upon ethnoveterinary interviews to discover opportunities for the future development of European veterinary herbal medicine. Material and methods: In 2018/2019 we conducted 77 semi-structured interviews with 101 farmers from different types of farms. Detailed information about homemade herbal remedies (plant species, plant part, manufacturing process, source of knowledge) and the corresponding use reports (target animal species, category of use, route of administration, dosage, source of knowledge, frequency of use, last time of use and farmers' satisfaction) were collected. To compare our data with the literature, the use reports of two local historical textbooks were analyzed and compared with the data from the interviews. Results: 716 homemade remedy reports (HRs) for altogether 884 use reports (URs) were documented in this study. We picked the 363 HRs that consisted of a single plant species with or without other natural products (HSHRs) for a deeper analysis. These HSHRs were prepared from 108 plant species that belonged to 57 botanical families. The most URs were documented for the families of: Asteraceae, Linaceae and Urticaceae. Calendula officinalis L. (Asteraceae), Linum usitatissimum L. (Linaceae) and Urtica dioica L. (Urticaceae) were the most often documented single species. A total of 448 URs were gathered for the 363 HSHRs. The largest number of URs was for treatments of gastrointestinal disorders and metabolic dysfunctions, followed by skin alterations and sores. For nearly half of the URs the source of knowledge was family and friends. For 80 URs the source of knowledge was different from that of the corresponding HSHRs. For 68% of the URs farmers mentioned at least one use during the last 5 years. Half of the plant species that were mentioned in the historical literature were also mentioned in URs by the interviewees. Conclusion: In Bavaria, medicinal plants are actively used by farmers to treat their livestock with a high level of satisfaction. The knowledge is not passed on from generation to generation in a purely static way, but is dynamically developed by the users in almost one fifth of the URs. Ethnoveterinary research combined with data from regional historical textbooks may facilitate pharmacological and clinical studies in veterinary medicine, and the discussion about a simplified registration for traditional herbal veterinary medicinal products. Graphical abstract: Image 1 Highlights: Ethnoveterinary research in Europe up North of the Alps. Historical veterinary textbooks with current farmer's knowledge on the treatment of livestock. Household remedies based on medicinal plants are still used today on Bavarian farms. Preserving traditional knowledge for the future development of veterinary phytotherapy. For today's animal health care: Translating tradition into modern veterinary medicine.